2020
DOI: 10.1364/oe.413674
|View full text |Cite
|
Sign up to set email alerts
|

Flat broadband chaos generation in a discrete-mode laser subject to optical feedback

Abstract: , Y. (Accepted/In press). Flat broadband chaos generation in a discrete-mode laser subject to optical feedback. Optics Express. Hawliau Cyffredinol / General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights. • Users may download and print one copy of any publication from the publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 37 publications
0
6
1
Order By: Relevance
“…When ξf > 0.063, the duration of the S becomes very short and the dynamic is about to leave the regular dynamical switching region. Compared with the previously reported intermittency in DFB lasers [25], regular multi-switches between S and P1 within a feedback round trip time during the dynamical route to chaos is observed for the first time in DM-SLs, and such regular multiple switches may result from the inter-cavity structure of DM-SLs [27][28][29][30] as well as the long ECF-induced instability. The further explorations are currently being undertaken in our research laboratory and corresponding results will be reported elsewhere in due course.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…When ξf > 0.063, the duration of the S becomes very short and the dynamic is about to leave the regular dynamical switching region. Compared with the previously reported intermittency in DFB lasers [25], regular multi-switches between S and P1 within a feedback round trip time during the dynamical route to chaos is observed for the first time in DM-SLs, and such regular multiple switches may result from the inter-cavity structure of DM-SLs [27][28][29][30] as well as the long ECF-induced instability. The further explorations are currently being undertaken in our research laboratory and corresponding results will be reported elsewhere in due course.…”
Section: Resultscontrasting
confidence: 56%
“…DM lasers can be used in coherent communication, optical sensing and terahertz wave generation resulting from their unique characteristics including very narrow linewidth emission, wide temperature range of operation, low cost and easy to integrate [28][29]. Although a DM-SL is less sensitive to external perturbations because of its special design of the intercavity structure, we recently experimentally generated a flat broadband chaos output from a DM-SL with amplified optical feedback [30]. However, the detailed dynamics in routes to chaos of the DM laser are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…A digital oscilloscope (OSC, Agilent DSO-X91604A, 16 GHz bandwidth) with a photodetector (PD, New Focus 1544B, 12 GHz bandwidth) is utilized to record the time series. The feedback strength is defined as the ratio of the feedback power to the output power of the free-running SL [26], where the feedback power is measured by a power meter (PM) through a port of FC1.…”
Section: Methodsmentioning
confidence: 99%
“…44 The flatness refers to the range of spectrum fluctuation within the bandwidth. In order to eliminate the influence of relaxation oscillation frequency on the bandwidth and flatness of chaotic laser, researchers have carried out extensive studies, including improved optical feedback, [45][46][47][48][49][50] unidirectional optical injection, [51][52][53][54][55][56][57][58][59] mutual injection, 60,61 and subsequent processing 62,63 of chaotic laser.…”
Section: Bandwidth Enhancementmentioning
confidence: 99%